Salivary alpha-amylase over cortisol ratio as a longitudinal indicator of work stress and psychosomatic strain in teachers - Schneider, Ida; Wettstein, Alexander; Jenni, Gabriel; Kühne, Fabienne; grosse Holtforth, Martin; Wachs, Sebastian; La Marca, Roberto (Frontiers in Endocrinology, 2025)
IntroductionThis longitudinal study investigates to what extent salivary alpha-amylase (as an index of the activation of the sympathetic nervous system, SNS), salivary cortisol (as an index of the activation of the hypothalamic-pituitary-adrenal, HPA, axis), and their ratio (reflecting asymmetry between both physiological stress systems) are valid indicators of stress in teachers. Moreover, we pose the question of whether dysregulation of the SNS and HPA axis is associated with individual risk and protective factors of teachers.MethodsSelf-report questionnaires were used to assess personality factors, coping strategies, and perceived psychological and psychosomatic strain, with the latter being reassessed two years later.ResultsThe results show that cross-sectionally, alpha-amylase is positively associated with individual risk factors and psychological strain in teachers, whereas cortisol showed no significant correlations. Longitudinally, however, the ratio of alpha-amylase over cortisol was the most consistent indicator of stress in teachers, with higher values predicting a more unfavorable stress experience and psychosomatic strain.DiscussionIn summary, an asymmetry between activity of the SNS and the HPA axis validly indicates work stress and psychosomatic strain in teachers.